Pengaruh Pelatihan dan Kompleksitas Tugas Pada Efektivitas Penggunaan SIA Rumah Sakit Swasta di Kota Denpasar - Dika Pradana, Gede Bagus; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 25 No 3 (2018), 2018)
Computer-based accounting information system is the right way to process accounting information systems to be more accurate, effective, and efficient. The purpose of this study was to determine the effect of training and the complexity of the task on the effectiveness of accounting information systems of private hospitals in Denpasar City. This research was conducted in 6 private hospitals in the city of Denpasar . The number of samples was 57 people using the saturated sample method. Data collection using questionnaires. Analysis used multiple linear regression test. Based on the results of the analysis it was found that training had a positive and significant effect on the effectiveness of the use of accounting information systems. This means that the more frequent the training, the higher the effectiveness of the use of accounting information systems. Task complexity has a positive and significant effect on the effectiveness of using accounting information systems. Keywords: training, task complexity, effectiveness of using accounting information systems.